The Causality Relationship of State Sukuk with Economic Growth in Indonesia and Malaysia - Fauzi, Ahmad; Qizam, Ibnu (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
Economic growth is an indicator of the success of a country's development. The higher the economic growth, the higher the welfare of society. Issuance of State Sharia Securities (SBSN) or State Sukuk as one of the APBN sources and is used to finance economic development in order to increase Gross Domestic Product (GDP). This research aims to determine the causality and long-term relationship between Government Sukuk (SBSN) and Economic Growth (GDP) in Indonesia and Malaysia. The method used in this research is the Vector Autoregression (VAR) model with quarterly data from 2009 to 2018. It is concluded that the relationship between SBSN and Indonesia's GDP is a unidirectional relationship where State Sukuk influences Indonesia's GDP. There is no causal relationship, either unidirectional or bidirectional, between Government Sukuk and Malaysian GDP. There is a long-term relationship between Government Sukuk and GDP in Indonesia and Malaysia. The importance of developing sukuk encourages financial inclusion, stimulates investment and economic growth.